Should evoked potential monitoring be used in degenerative cervical spine surgery? A systematic review - Alberto Di Martino; Rocco Papalia; Antonio Caldaria; Guglielmo Torre; Luca Denaro; Vincenzo Denaro (Journal of Orthopaedics and Traumatology, 2019)
Abstract Background Intraoperative somatosensory evoked potential (SSEP) and transcranial motor evoked potential (tcMEP) monitoring are frequently used in spinal as well as spinal cord surgery for so-called intraoperative neuromonitoring (IONM), while the combination of these techniques is known as concomitant multimodal intraoperative monitoring (MIOM). The aim of this review is to collect available evidence concerning use of IONM and MIOM in cervical decompression surgery in the degenerative setting and attempt to identify the best practice to be advocated. Materials and methods A review of the PubMed and MEDLINE databases and Cochrane Central Registry of Controlled Trials was performed. Studies were included if they involved patients who underwent cervical spine decompression surgery for degenerative stenosis with use of IONM or MIOM and where sensitivity/specificity was reported. Results In the identified studies, the sensitivity of SSEP was estimated to be between 22 and 100% with constant specificity of 100%. In the included studies, the sensitivity of MEP was estimated to be between 78 and 100% with specificity ranging from 83.2 to 100%. Conclusions On the basis of available evidence, MIOM could be a helpful tool in decompression cervical spine surgery in patients affected by degenerative spinal stenosis, since it is associated with high specificity and sensitivity for detection of intraoperative neural damage. However, evidence is still lacking regarding patient selection to identify individuals in whom monitoring is indicated. Level of evidence IV (systematic review of studies with LOE II to IV).